Rainfall Extremes, Distribution and Properties - Abbot, John; Hammond, Andrew (IntechOpen, 2019)
This book describes aspects of rainfall including the extremes, distribution and properties. The introductory chapter focusses on drought and flooding rains over Australia, placing extreme rainfall events from recent decades into a historical context using reconstructions from proxy data. The next three chapters focus on distribution and impacts of rainfall. The first of these chapters presents a statistical analysis of rainfall patterns for Jeddah City and considers future impacts. The second examines rainfall in the context of impacts, vulnerability and climate change in eastern Africa. The third examines extreme rainfall and drought in the Asia-Pacific, through application of monitoring from space. The final chapters focus on properties of rain, one examining aerosol-cloud-precipitation interactions, while another considers the chemical nature of individual size-resolved raindrops.